Measurement issues in conflict event data: Addressing some misconceptions about what drives differences between human-coded event datasets - Magnus Öberg; Mert Can Yilmaz (Research & Politics)
Clionadh Raleigh, Roudabeh Kishi, and Andrew Linke recently compared their own Armed Conflict Location and Events Dataset (ACLED) to three other conflict event datasets in Humanities & Social Sciences Communications. In this article, we investigate their claims about what drives differences between the two researcher led projects the Uppsala Conflict Data Program (UCDP) and ACLED. In the process, we address some general issues that arise in event data collection, including the importance of stable definitions, how demands on sourcing varies with the type of data collected, and how strategies for dealing with uncertainty and ambiguity impact the data. Contrary to the claims made in the target article, the differences between ACLED and UCDP in the cases put forth by the authors are not primarily due to differences in sourcing or inclusion thresholds. Analyzing the same cases, we show that most of the differences are due to auxiliary coding rules, standards for source evaluation and misrepresentations of UCDP data in the original article.